ANALISIS DAN VISUALISASI PERSAMAAN KLEIN-GORDON PADA ELEKTRON DALAM SUMUR POTENSIAL DENGAN MENGGUNAKAN PROGRAM MATHEMATIC 10 - Syahrul Humaidi; Tua Raja Simbolon; Russell Ong; Widya Nazri Afrida (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Schrödinger equation is a wave equation that describes the behaviour of an electron including determining its energy levels. However, when the motion of electrons was assumed as relativistic motion(vc), then the schrödinger equation must be changed into Klein-Gordon equation(relativistic Schrödinger equation). In order to compare both equations, we analyzed and visualized the Klein-Gordon equation for an electron in a potential well with Wolfram Mathematica 10 software. The visualization from Mathematica 10 gave the same wavefunction graphs and probability density graphs as the Schrödinger equation. The difference is only in the visualization of energy levels graphs. Keywords:Klein-Gordon equation, Mathematica 10, electron, energy levels.